Avaliação de impactos ambientais do setor têxtil por meio da ACV (avaliação do ciclo de vida) estudo de caso : calça jeans - Morita, Amelia Masae (2013)
The purpose of this study was evaluating the environmental impacts in jeans production using the method called Life Cycle Assessment (LCA). The LCA is a technique used to study the environmental impacts generated by a product or process, since the raw materials to final disposal. These impacts can be specific like eutrophication of a river by emissions of an industry, or global like global warming and ozone layer depletion. The studies were conducted from extraction of the fiber to the finished part and the reference flow is the production of a jeans. The results were obtained using software SimaPro7TM and they demonstrated that the production of raw material (cotton) and the use of thermal energy in dyeing / weaving and finishing cause the greatest impact in the production of jeans. The categories of impact most influenced by cotton production were climate change, ozone depletion, terrestrial ecotoxicity, freshwater ecotoxicity, photochemical oxidant formation and particulate matter formation, terrestrial acidification, freshwater eutrophication, agricultural land occupation, minerals depletion and fossils depletion, while the categories human toxicity and urban land occupation are influenced by the sectors of dyeing / weaving and finishing. The category of virgin land transformation is strongly influenced by the use of electricity, mainly in the spinning. The reduction of these impacts can be obtained by improving the techniques of soil management and reducing the use of chemicals in the cultivation of cotton, besides seeking energy alternatives and optimize the processes of dyeing and finishing. Despite the lack of Brazilian?s inventories on thermal power generation and the production of chemicals such as fertilizers and chemicals specific to the textile area, the present study identified the raw material production and dyeing and finishing sectors responsible for the major impacts of jeans. In addition, the most significant impact categories were terrestrial and aquatic ecotoxicity, freshwater eutrophication and human toxicity.